Catering Students Acceptance Towards the Use of Smartphone Application in Food Presentation - Siti Hajar binti Zakariah; Md Sahak, Adibah Aishah; Anuar, Nurul Azlinda; Abdul Rahman, Abdul Wafi (Research and Innovation in Technical and Vocational Education and Training, 2021)
Today’s technological advancements have brought many changes, especially the use of the Internet in education. Learning to use a smartphone app is a learning approach that addresses knowledge and skills acquisition through mobile technology. The purpose of this study is to measure (1) student acceptance factors in the application of learning (2) the impact of student acceptance on application usage and (3) the level of student acceptance in application usage for the study of the art of food presentation. This study was conducted on a sample of 60 undergraduate students. The students were from Faculty of Technical and Vocational, University Tun Hussein Onn Malaysia (UTHM). A set of questionnaire was used as an instrument. The data was descriptive analysis using Statistical Package for Social Science (SPSS) version 18. Percentage, mean and standard deviation were obtained from the analysis process. In this research finding, it showed that the factors of student acceptance in the application of learning, the impact of student acceptance in application usage and the level of student acceptance in the application of learning for the presentation of the art of food presentation are respectively high with mean scores of 4.08, 3.81 and 4.00. According to the results, some suggestions for further research to enable application learning are also highlighted.